Temporal and spatial adjustments of channel migration and planform geometry: responses to ENSO driven climate anomalies on the tropical freely-meandering Aguapeí River, São Paulo, Brazil - Suizu, Tainá Medeiros [UNESP]; Nanson, Gerald C. (Wiley, 2018)
Two reaches of Aguapeí River, a left-bank tributary of the Paraná River in western São Paulo state, Brazil, were studied with the objective of assessing the role of bend curvature on channel migration in this wet-tropical system and examining if land-use changes or ENSO (El Niño Southern Oscillation) driven climate anomalies over nearly half a century have changed migration behaviour and planform geometry. Meander-bend migration rates and morphometric parameters including meander-bend curvature, sinuosity, meander wavelength and channel width, were measured and the frequency of bend cutoffs was analysed in order to determine the rate of change of channel adjustment over a 48 year period to 2010. Results show that maximum average channel migration rates occur in bends with curvatures of about 2–3 rc/w, similar to other previously studied temperate and subarctic freely meandering rivers although not as pronounced and with a tendency to favour tighter curvature. From 1962 to 2010 the Aguapeí River has undergone a significant reduction in sinuosity, a shift from tightly curving to more open bends, an overall decline in channel migration rates, an associated decrease in the frequency of neck-cutoffs and an overall increase in channel width. As the majority of the drainage basin (96%) was already deforested in 1962, channel form and process changes were, unlike an interpretation for an adjacent river system, not attributed to altered land-use but rather to a sharp ENSO-driven increase in the magnitude of peak flow-discharges of some 32% since 1972. In summary, this research revealed that recent climate and associated flow regime changes are having a pronounced effect on river channel behaviour in the Aguapeí River investigated here. Copyright © 2018 John Wiley & Sons, Ltd.
Keywords: Aguapeí River; channel migration; channel planform-change; ENSO climate-change; freely-meandering rivers